2010
DOI: 10.1007/s00027-010-0162-7
|View full text |Cite
|
Sign up to set email alerts
|

Response of aquatic plants to abiotic factors: a review

Abstract: This review aims to determine how environmental characteristics of aquatic habitats rule species occurrence, life-history traits and community dynamics among aquatic plants, and if these particular adaptations and responses fit in with general predictions relating to abiotic factors and plant communities. The way key abiotic factors in aquatic habitats affect (1) plant life (recruitment, growth, and reproduction) and dispersal, and (2) the dynamics of plant communities is discussed. Many factors related to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
437
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(457 citation statements)
references
References 193 publications
(171 reference statements)
13
437
1
6
Order By: Relevance
“…That could be a possible explanation for the observed negative correlation for biomass ratio and turbulence. A similar trend was previously observed for Valisnaria spiralis after exposure to turbulence under laboratory conditions (Ellawala et al, 2013), whereas a similar field observation was also reported for some other aquatic plant species (Asaeda et al, 2010b;Bornette, Puijalon, 2011).…”
Section: Turbulence Biomass Ratiosupporting
confidence: 89%
See 1 more Smart Citation
“…That could be a possible explanation for the observed negative correlation for biomass ratio and turbulence. A similar trend was previously observed for Valisnaria spiralis after exposure to turbulence under laboratory conditions (Ellawala et al, 2013), whereas a similar field observation was also reported for some other aquatic plant species (Asaeda et al, 2010b;Bornette, Puijalon, 2011).…”
Section: Turbulence Biomass Ratiosupporting
confidence: 89%
“…For instance, water level fluctuations strongly affect to the growth of macrophytes in middle and lower eulittoral zone (Krolova et al, 2013). Different responses for these circumstances, including variations in biomass allocation, plant growth and morphological variations, have been exhibited in plants (Asaeda et al, 2010a,b;Bornette, Puijalon, 2011;Silinski et al, 2015). Flow regimes and hydraulics are commonly cited as the main abiotic determinants that affect the architecture of the aquatic systems by altering the distribution and assemblages of plant communities (Chambers et al, 1991;Green, 2005;Olson et al, 2012;Thomaz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of light for photosynthesis is one of the most important environmental factors regulating aquatic plant growth (Sand-Jensen, 1989;Bornette and Puijalon, 2011) and water clarity frequently shapes species composition in macrophyte communities (Hawes et al, 2003). Due to the reduced light availability in deeper water, depths greater than 4 m are marginal habitat for C. caroliniana.…”
Section: Discussionmentioning
confidence: 99%
“…Capers (2003) found that about 60% of the individuals that colonised bare soil in freshwater tidal areas originated from vegetative propagules. Genetic studies, however, show that recruitment from vegetative propagules versus seeds and oospores is very species specific (Nilsson et al, 2010;Bornette & Puijalon, 2011).…”
Section: Germinationmentioning
confidence: 99%
“…We focus on the importance of biotic factors, including the availability of propagules, the amount of herbivory and role of remnant populations, whereas macrophyte requirements for abiotic conditions, such as light and nutrient availability or shelter from the wind are recently reviewed in Bornette & Puijalon (2011). Furthermore, we address the importance of the composition and abundance of the macrophyte vegetation as these may affect the performance of ecosystem functions and conservation value of the vegetation.…”
Section: Introductionmentioning
confidence: 99%